2022
DOI: 10.1186/s12974-022-02458-2
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-based delivery of interleukin-13 improves functional and histopathological outcomes following spinal cord injury

Abstract: Background Spinal cord injury (SCI) elicits a robust neuroinflammatory reaction which, in turn, exacerbates the initial mechanical damage. Pivotal players orchestrating this response are macrophages (Mφs) and microglia. After SCI, the inflammatory environment is dominated by pro-inflammatory Mφs/microglia, which contribute to secondary cell death and prevent regeneration. Therefore, reprogramming Mφ/microglia towards a more anti-inflammatory and potentially neuroprotective phenotype has gained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…In addition, longterm neurodevelopment improves directly correlates to the serum decrease maintained over time. The role of IL-13 in brain damage is still unclear and the interpretation of its plasma levels is controversial, since recent animal experimentation attributes to this cytokine: anti-inflammatory and neuroprotective effects [53,54], reactivation of neuronal pyroptosis and increased neurological deficits in models of cerebral hemorrhage [55,56]. In a recent clinical trial in asphyxiated human neonates, Massaro et al observed that an early plasma increase (24 hours) of cytokines such as IL-1 and IL-13 was related to greater brain injury as seen on magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, longterm neurodevelopment improves directly correlates to the serum decrease maintained over time. The role of IL-13 in brain damage is still unclear and the interpretation of its plasma levels is controversial, since recent animal experimentation attributes to this cytokine: anti-inflammatory and neuroprotective effects [53,54], reactivation of neuronal pyroptosis and increased neurological deficits in models of cerebral hemorrhage [55,56]. In a recent clinical trial in asphyxiated human neonates, Massaro et al observed that an early plasma increase (24 hours) of cytokines such as IL-1 and IL-13 was related to greater brain injury as seen on magnetic resonance imaging.…”
Section: Discussionmentioning
confidence: 99%
“…A standardized T-cut spinal cord hemisection injury was performed as previously described [1820]. In brief, mice were anesthetized with 2-3% isoflurane and a partial laminectomy was performed at thoracic level 8.…”
Section: Methodsmentioning
confidence: 99%
“…Inhibition of PDE4B suppresses the neuroinflammatory responses of macrophages and microglia, while PDE4D blockage has been shown to successfully boost myelin regeneration and enhance neuroplasticity [13][14][15][16]. Targeting these individual subtypes circumvented the emetic side-effects accompanied by pan PDE4 inhibitors such as roflumilast and rolipram, and is predicted a valuable strategy to target neuroinflammation [17].…”
Section: Introductionmentioning
confidence: 99%
“…These procedures are followed by physical therapy to improve independence in daily living and reintegration into society [ 86 ]. Besides the general clinically approved therapies ( Figure 4 ), new state-of-the-art treatments are being developed to stimulate neuroprotection and neuroregeneration or improve function using neuroprosthetics or neurostimulation [ 87 , 88 , 89 , 90 ]. Despite these continued efforts to find an effective treatment, current strategies do not cure SCI and induce limited functional recovery, highlighting the need for alternative and complementary approaches to treat SCI patients.…”
Section: Dna Repair Is An Attractive Therapeutic Target In Scimentioning
confidence: 99%